Mechanisms of Magnetization Reversal in Stadium-Shaped Particles - Altbir-Drullinsky, D; Allende-Prieto, S; Vargas-Ayala, N; Castillo-Sepulveda, S (2012)
During the last years, cylindrical structures like dots, wires, and tubes have been intensively investigated. However, stadium-shaped particles have been scarcely investigated because of the complexity associated to the control of its geometry. In this paper, we used a scaled atomistic representation with Monte Carlo simulations to investigate systematically the magnetization reversal process in stadium-shaped magnetic structures as a function of the size of the central volume. Different reversal mechanisms have been identified and its existence has been explained. The reversal process for short, almost circular, stadium structures occurs via the formation of a single vortex, whereas for longer stadium structures the reversal process involves either single vortices or vortex pairs. For the longest structures investigated, the reversal always involves two vortices that generate a central diamond region or a central antivortex, depending on the region of the nucleation of the vortices. Our results provide guidelines for the use of stadium-shaped particles in the control of vortex motion when a magnetic field is applied. © 2012 American Institute of Physics.